2018
DOI: 10.1002/slct.201702597
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Pd/POSS Nanocatalysts for C–C Cross‐Coupling Reactions

Abstract: An insoluble solid support of N−heterocyclic imidazolium‐functionalized cage‐like silsesquioxane (SQ); Bim‐SQ, was synthesized by nucleophilic substitution of octakis(3‐chloropropyl)octasilsesquioxane with an excess bis‐(imidazol‐1‐yl)methane and investigated as a new organic‐inorganic hybrid support. In the presence of Bim‐SQ, Pd(II) from [PdCl4]2− can be stabilized via both electrostatic interactions and imidazole‐N‐coordination, giving an amorphous material of Pd(II)@Bim‐SQ. Subsequent in situ reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…Imidazolium‐containing POSS was synthesized and used to stabilize Pd nanoparticles via both electrostatic interactions and imidazloe‐N‐coordination. The obtained Pd@POSS nanoparticles worked as an active heterogeneous catalyst for Suzuki–Miyaura cross‐coupling reactions and Heck reactions with good reusability …”
Section: Advanced Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imidazolium‐containing POSS was synthesized and used to stabilize Pd nanoparticles via both electrostatic interactions and imidazloe‐N‐coordination. The obtained Pd@POSS nanoparticles worked as an active heterogeneous catalyst for Suzuki–Miyaura cross‐coupling reactions and Heck reactions with good reusability …”
Section: Advanced Applicationsmentioning
confidence: 99%
“…The obtained Pd@POSS nanoparticles worked as an active heterogeneous catalyst for Suzuki-Miyaura cross-coupling reactions and Heck reactions with good reusability. [98] Through a green synthetic methodology without the addition of an alkali solution, Mohapatra's group fabricated octakis(3-(1-methylimidazolium) propyl) octasilsesquioxane (POSS-MPIm)-supported palladium NPs. As shown in Figure 3, POSS-MPImCl reacted with Pd(OAc) 2 for 72 h at 100 °C via a solid state annealing process to form Pd(II)-MPIm-POSS (1).…”
Section: Ssqs For Catalystmentioning
confidence: 99%
“…In the preparation of silsesquioxane-based porous polymers,w hether cubic cages keep intact or not depends on many factors, for example, monomer types, reactiont ype or condition etc. Usually, cage tends to collapsei no rder to release structurals tress in the stiff network formed by Heck, Sonogashira,S uzuki and Ullmann reactiona nd hierarchicalp orous structures easily formed; [9,19] however,t he flexible linking units helpt ok eep cage intact and bimodal pore structures usually formed, for ex-ample,s ome silsesquioxane-based porous polymers, which are prepared by the Friedel-Crafts reaction of octavinylsilsesquioxane with aromatic compounds to form the flexible linker of CH 2 -CH 2 -Ar. [7a] The destruction of cage in this case might be due to the following factors.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…[10] On the contrary, the heterogeneous Pd NPs catalysts require only molecular oxygen as oxidant and are reusable with usually low metal contamination in the oxidized products. [11][12][13] Although chemically robust, N-rich aromatic triazole compounds have been demonstrated as good stabilizers for MNPs, [14] only a handful of examples involving Pd NPs catalysts supported by triazole-functionalized solid supports have so far been reported. [11][12][13] Although chemically robust, N-rich aromatic triazole compounds have been demonstrated as good stabilizers for MNPs, [14] only a handful of examples involving Pd NPs catalysts supported by triazole-functionalized solid supports have so far been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that Pd NPs stabilized by functionalized polyhedral oligomeric silsesquioxanes (POSS) serve as active catalysts for aerobic alcohol oxidation and Suzuki-Miyaura cross coupling reactions. [11][12][13] Although chemically robust, N-rich aromatic triazole compounds have been demonstrated as good stabilizers for MNPs, [14] only a handful of examples involving Pd NPs catalysts supported by triazole-functionalized solid supports have so far been reported. [15][16][17][18][19] Notably, Astruc and co-workers showed that Pd NPs stabilized on tris (triazolyl)-functionalized silica-coated magnetic supports could quantitatively convert benzyl alcohol to benzaldehyde in toluene at 90°C in air.…”
Section: Introductionmentioning
confidence: 99%